2016
DOI: 10.3390/molecules21121616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of the Inhibition Effect of Astragaloside IV and Aglycone Cycloastragenol on Various UDP-Glucuronosyltransferase (UGT) Isoforms

Abstract: As one of the main active ingredients from Radix Astragali (RA), orally dosed astragaloside IV (AST) is easily transformed to sapogenin-cycloastragenol (CAG) by deglycosylation in the gastrointestinal tract. Because the potential adverse effects of AST and CAG remain unclear, the present study in this article was carried out to investigate the inhibition effects of AST and CAG on UDP-glucuronosyltransferases (UGTs) to explore potential clinical toxicity. An in vitro UGTs incubation mixture was employed to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Inhibition of drug-metabolic enzymes in drug combination therapies is considered an important origin of adverse effects. It can lead to withdrawal of several approved drugs from the markets, causing clinical problems and economic losses [ 7 , 26 ]. Along with the upsurge of herb–drug combinations, inhibition of herbs towards drug-metabolic enzymes in HDIs has been raised as an important reason that limits clinical applications of herbs and drugs [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of drug-metabolic enzymes in drug combination therapies is considered an important origin of adverse effects. It can lead to withdrawal of several approved drugs from the markets, causing clinical problems and economic losses [ 7 , 26 ]. Along with the upsurge of herb–drug combinations, inhibition of herbs towards drug-metabolic enzymes in HDIs has been raised as an important reason that limits clinical applications of herbs and drugs [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…UGTs are phase II metabolic enzymes that predominantly catalyze glucuronidation of xenobiotics, including approximately 35% of drugs and consequently, facilitating elimination of glucuronidated metabolites through bile and urine [ 6 , 7 ]. Glucuronidation clears drugs because glucuronidated metabolites have more polarity and water solubility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, it was found that MGF and NTR activated UGT 1A10 and deglycosylation of MGF into NTR strongly increased the inhibitory effects towards others tested UGT isoforms except UGT1A10. The deglycosylation of saponin to aglycone always exhibited a different inhibition profile, such as astragaloside IV and cycloastragenol, glucoaurantio-obtusin and aurantio-obtusin, liquiritin and liquiritigenin, icariin and its intestinal metabolites (icariside I, icariside II and icaritin), arctiin and arctigenin, scutellarin and scutellarein, and in most situations, aglycone showed stronger inhibitory effects than saponin [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In our study, in silico docking method was used to explain why the inhibition potential of NTR was stronger than MGF on the activity of UGT1A3, UGT1A7 and UGT1A9.…”
Section: Discussionmentioning
confidence: 99%
“…Fluconazole itself is not metabolized by UGT but alter pharmacokinetic parameters of co-administrated zidovudine in AIDS patients, because the glucuronidation of zidovudine by UGT2B7 is strongly inhibited by fluconazole [ 32 ]. Cycloastragenol has been proven to specifically inhibit UGT1A8 and UGT2B7, thus affecting drugs undergoing UGT1A8- and UGT2B7-catalyzed metabolism [ 33 ].…”
Section: Introductionmentioning
confidence: 99%